2019
DOI: 10.2355/isijinternational.isijint-2018-470
|View full text |Cite
|
Sign up to set email alerts
|

Water Gas Shift Reaction and Effect of Gasification Reaction in Packed-bed under Heating-up Condition

Abstract: The single WGSR in alumina crucible is in an equilibrium state over 1 573 K. Calculation of gasification reaction (K B , Boudouard reaction) in Zone 1 and Zone 1 + 2 + 3 were in excellent agreement with the observation under CO-CO 2 system (without Hydrogen). When H 2 was added to the reaction gases, Water gas reaction I (K W1) and II (K W2) in addition to K B were calculated separately and the total gasification reaction RCS cal (= K B + K W1 + K W2) was in good agreement with the observation. The relationshi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
1
1
0
Order By: Relevance
“…Ono-Nakazato et al 25) found that the contribution of the water-gas shift reaction (WGST) was estimated to be 3% against its equilibrium at a low reduction temperature below 1 200 K, and similar results found by T. Kon et al 26) This mean that at low temperature the influence of the water gas shift on the reduction was small but at high temperature ( > 1 273 K) the total water gas shift was largely changed. 27) In our current study, the reduction ranged from 1 023 to 1 223 K (750-950°C) where the contribution of WGST was small on the equilibrium based on the results found in the literature. However, based on the different reduction activities between H 2 and CO below and above 810°C, the effect of WGST on the reduction and the heat transfer analysis was added as well.…”
Section: Mathematical Modelsupporting
confidence: 75%
“…Ono-Nakazato et al 25) found that the contribution of the water-gas shift reaction (WGST) was estimated to be 3% against its equilibrium at a low reduction temperature below 1 200 K, and similar results found by T. Kon et al 26) This mean that at low temperature the influence of the water gas shift on the reduction was small but at high temperature ( > 1 273 K) the total water gas shift was largely changed. 27) In our current study, the reduction ranged from 1 023 to 1 223 K (750-950°C) where the contribution of WGST was small on the equilibrium based on the results found in the literature. However, based on the different reduction activities between H 2 and CO below and above 810°C, the effect of WGST on the reduction and the heat transfer analysis was added as well.…”
Section: Mathematical Modelsupporting
confidence: 75%
“…The effect of hydrogen in the blast furnace atmosphere has been studying. [20][21][22][23][24][25][26][27] However, the studies that observed data in the blast furnace with the huge amount of hydrogen injection operation is few. In this paper, the results of campaigns taken placed in 2018fy to 2020fy were reported.…”
Section: Influence Of Large Amount Of Hydrogen Containing Gaseous Red...mentioning
confidence: 99%